Ajíes Nativos Peruanos - Caracterización Agro-morfológica, químico - nutricional y sensorial - Quispe Jacobo, Fredy Enrique; Rojas, Rosario; Patel, Kirti; Ruíz, Candy; Calderón, Rosa; Ascencios, Edgard; Marcelo Salvador, Mavel (Universidad Peruana Cayetano Heredia, 2020)
136 Páginas.